2012
DOI: 10.1016/j.jhevol.2012.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Inland human settlement in southern Arabia 55,000 years ago. New evidence from the Wadi Surdud Middle Paleolithic site complex, western Yemen

Abstract: The recovery at Shi'bat Dihya 1 (SD1) of a dense Middle Paleolithic human occupation dated to 55 ka BP sheds new light on the role of the Arabian Peninsula at the time of the alleged expansion of modern humans out of Africa. SD1 is part of a complex of Middle Paleolithic sites cut by the Wadi Surdud and interstratified within an alluvial sedimentary basin in the foothills that connect the Yemeni highlands with the Tihama coastal plain. A number of environmental proxies indicate arid conditions throughout a seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 87 publications
1
91
0
Order By: Relevance
“…This hypothesis has clear parallels with Dennell and Roebroek's (2005) concept of "Savannahstan," with initial hominins dispersing into Asia remaining within African-like environments. Later (∼55 ka) sites from the Arabian peninsula during arid intervals lack Nubian Type 1 cores and suggest instead the development of regionally distinct variants in Arabia and Africa with environmental change (Delagnes et al 2012). …”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis has clear parallels with Dennell and Roebroek's (2005) concept of "Savannahstan," with initial hominins dispersing into Asia remaining within African-like environments. Later (∼55 ka) sites from the Arabian peninsula during arid intervals lack Nubian Type 1 cores and suggest instead the development of regionally distinct variants in Arabia and Africa with environmental change (Delagnes et al 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Palaeohydrology is key to understanding the dispersal of hominins into the Arabian Peninsula during the Quaternary, and for exploring hypotheses relating to the expansion and contraction of Palaeolithic populations both within Arabia and between regional refugia (Petraglia and Alsharekh, 2003;Field and Lahr, 2006;Rose and Petraglia, 2009;Armitage et al, 2011;Petraglia et al, 2011Petraglia et al, , 2012Delagnes et al, 2012;Petraglia, 2012, 2014;Crassard et al, 2013aCrassard et al, , 2013bScerri et al, 2014b). Surface freshwater availability, mediated by periodic incursions of increased rainfall, is likely to have been a critical control on the timing and routeways of hominin migrations across the mid-latitude SaharoArabian desert belt.…”
Section: Palaeohydrology and Hominin Dispersals In The Arabian Peninsulamentioning
confidence: 99%
“…392 m. Three sites (Shi'bat Dihya 1: SD1, Shi'bat Dihya 2: SD2, Al-Sharj1: AS1) have been investigated, ranging between ca. 60 and 50 ka (see Delagnes et al, 2012), and scattered lithics have been found in a lower geological unit dated to ca. 85 ka.…”
Section: Wadi Surdud Regional Settingmentioning
confidence: 99%
“…These stages correspond to hyperarid episodes with subsequent cessation of alluvial sedimentation and formation of desert pavements. The incision phases in the basin that separate the different sedimentary members are assumed to result from high water flux periods in the Delagnes et al, 2012) and the Wahiba sands of Oman (from Preusser, 2009). The content of biogenic CaCO 3 in core 70 KL is inversely correlated with the contribution of dust in the Arabian sea (from Leuschner and Sirocko, 2003); the curve of the summer insolation difference between 30 S and 30 N is a measure of the intensity of the Indian monsoon (from Leuschner and Sirocko, 2003); after Sitzia et al, 2012. Wadi, corresponding to the humidity peaks documented during MIS 5e (128e120 ka), MIS 5c (110e100 ka) and MIS 5a (90e74 ka) in the Arabian Peninsula, as well as during the beginning of the Holocene (Fleitmann and Matter, 2009;Fleitmann et al, 2011;Rosenberg et al, 2011).…”
Section: Environmental Context 55000 Years Agomentioning
confidence: 99%
See 1 more Smart Citation